Ecosystem management of the Leopard coralgrouper (Plectropomus spp.) population within the Sugud Islands Marine Conservation Area (SIMCA) - Chung, Fung Chen (2015)
Surveys have indicated that reef fish populations have declined in Sabah Malaysia. Several species of large-size groupers (Serranidae) have been heavily targeted to support the live reef fish food trade (LRFFT). Reef fishes that form aggregations for spawning or other purposes are vulnerable to fishery. The coral trout (Plectropomus leopardus ) is one of those species that aggregates at the time of spawning. Despite the importance of large-sized groupers to fishery, very little is known about how the species respond ecologically to the marine reserve protection. This study consisted of four main research objectives: 1) To determine if coral trouts (Plectropomus leopardus, P. oligacanthus, and P. maculatus , referred as Plectropomus spp.) respond positively to reserve protection; 2) To determine spatial and temporal aggregation pattern of Plectropomus leopardus; 3) To determine if substrate quality and prey density are associated with the aggregation and distribution of Plectropomus leopardus, and 4) To determine hydrodynamic conditions during reproductive season of Plectropomus leopardus . Study was conducted at Lankayan Island which is located within the Sugud Islands Marine Conservation Area (SIMCA). Plectropomus spp. responds positively to marine reserve protection with mean abundance count inside the reserves three-times greater than outside. A total of 56 Plectropomus spp. Were recorded in 12,000 m2 survey areas, with mean 1.17 fish per every 250 m2. Plectropomus leopardus represents 80% of total count. Plectropomus oligacanthus and P. maculatus mean abundance were relatively low. Larger Plectropomus spp. was recorded at patch reefs within 3 to 5 Kilometres from Lankayan Island. This indicated that low to no fishing activities inside marine reserve allowed to maintain more and larger Plectropomus spp. up to 5 Kilometres from Lankayan Island. The hard coral cover was recorded high inside the reserve, and regression analysis indicated decreased percentage of hard coral cover with increased distance from Lankayan Island. However, no relationship was detected between the hard coral cover and the Plectropomus spp. abundance. Plectropomus leopardus aggregated to spawn and to feed. Aggregation of P. leopardus was correlated with moon phases and underwater current strength. About 80% of the recorded aggregation was for feeding purposes. Peak feeding aggregation reached 61 individual fish in 1000 m2. While aggregation for spawning was noticed during new moon from April to August. Plectropomus leopardus displayed four different body colorations during aggregation: 1) dark, 2) pale, 3) olive-green and 4) patterned. Correlation analysis indicated that the larger fish tended to be in darker phase. However, behaviour observations during aggregation indicated that coloration changes might not indicate individual sex but rather tendency and readiness to spawn. Large males with darkening fins edges described earlier were rare during the spawning aggregation. I speculated that the large male with darkening fins edge is a dominant individual that leads the spawning population and this role could be a signal for reproductively active fishes in get into readiness mode for spawning. This study also recorded intra- and inter-specific cooperative hunting between Plectropomus leopardus with the other piscivorous species such as Caranx melampygus, Carangoides bajad, P. oligacanthus, P. maculatus, Lutjanus russelli, Fistularia commersonii on juvenile transient prey fishes (Pterocaesio tessellate, Pterocaesio diagramma, Dipterygonatus balteatus and Atherinomorus lacunosus ). The distribution of Plectropomus leopradus was associated with the density of transient prey species population abundance. The prey density predicted P. leopardus density. However, the current direction was not a significant indicator that could be used for prediction. Meanwhile, transient prey fish's density was associated with the direction of the underwater currents. Transient prey fishes aggregated at reef sides that received current from sides running parallel off the reef. However, the aggregation and distribution of P. leopardus was not associated with the underwater current direction. There was no relation with the substrate quality, surface roughness, crevice number and volume between aggregation and non-aggregation sites. Thus, substrate quality and habitat complexity do not seem to affect P. leopardus distribution. However, aggregation site contained higher percentage of encrusting coral life form. Presumably encrusting coral life form provides more hole and large crevices compared to other coral life forms. The moon phases that appeared to affect fish aggregation to spawn probably operated through tidal fluctuations. The hydrodynamic conditions in spring tide during full and new moon indicated higher surface current speed compared to neap tide. Increased surface currents were recorded during full moon and new moon from April to June. Typically after dusk, surface current increased during lowest ebb tide when the tide started to rise. High surface current during spring tides from April to June could be an important environmental drive to transport eggs and larvae to distant reefs. The ocean hydrodynamics is typically complex and is linked with other environmental factors such as wave, wind and topographical factors. Modelling on current speed and direction allow predictions on the possible dispersal of eggs and larvae. Understanding of the hydrodynamic pattern provided a basis to establish connectivity, recruitment and the source-sink habitats within and surrounding the marine reserve.